213k views
3 votes
What is the recursive rule for the sequence?

−2.7, −8.3, −13.9, −19.5, −25.1




an=an+1+5.6, where a1=−2.7

an=an+1−5.6, where a1=−2.7

an=an−1+5.6, where a1=−2.7

an=an−1−5.6, where a1=−2.7

What is the recursive rule for the sequence? −2.7, −8.3, −13.9, −19.5, −25.1 an=an-example-1
User Visual
by
5.3k points

1 Answer

6 votes

Answer:


a_(n) =a_(n-1) -5.6 where
a_(1) =-2.7

Explanation:

This is an arithmetic sequence with the first term is
a_(1) = -2.7 and has a common difference of
d=-5.6.

Arithmetic Sequence:
a_(n) =a_(n-1) +d


a_(n) is the nth term and
d is the common difference.

The common difference: -2.7, -8.3, -13.9...

Subtract: -2.7- (-8.3) = -5.6, -13.9 - (-8.3) = -5.6

Common difference:
d = -5.6

Recursive rule:
a_(n) = a_(n-1) -5.6

User Walterfaye
by
6.7k points